1997
DOI: 10.7557/2.17.3.1359
|View full text |Cite
|
Sign up to set email alerts
|

Rangifer population ecology: a Scandinavian perspective

Abstract: Population ecology is concerned with measuring changes in population size and composition, and identifying the causes of these fluctuations. Important driving variables include animal body size and growth rate, and their relationship to reproduction and mortality. Among wild and domestic reindeer (Rangifer tarandus tarandus), reproductive performance, calving time, calf birth weight and neonatal mortality are strongly correlated to maternal weight. Heavy females enjoy higher pregnancy rates, calve earlier, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
1
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 45 publications
3
78
1
6
Order By: Relevance
“…Calf growth rates observed in this study were higher than those found on high quality Scandinavian ranges (Reimers, 1997). Winter calf weights observed were high, 60.1 kg for males, compared to male calf autumn weights reported for Scandinavian reindeer herds, 31.6-54.5 kg, (Reimers, 1997); and 55.9 kg for females compared to female calf winter weights from reindeer introduced onto South Georgia (41-48kg), (LeaderWilliams Leader-Williams & Ricketts, 1982).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Calf growth rates observed in this study were higher than those found on high quality Scandinavian ranges (Reimers, 1997). Winter calf weights observed were high, 60.1 kg for males, compared to male calf autumn weights reported for Scandinavian reindeer herds, 31.6-54.5 kg, (Reimers, 1997); and 55.9 kg for females compared to female calf winter weights from reindeer introduced onto South Georgia (41-48kg), (LeaderWilliams Leader-Williams & Ricketts, 1982).…”
Section: Discussioncontrasting
confidence: 81%
“…Winter calf weights observed were high, 60.1 kg for males, compared to male calf autumn weights reported for Scandinavian reindeer herds, 31.6-54.5 kg, (Reimers, 1997); and 55.9 kg for females compared to female calf winter weights from reindeer introduced onto South Georgia (41-48kg), (LeaderWilliams Leader-Williams & Ricketts, 1982). Male calves had higher rates of growth than female calves in accordance with other studies (Haukioja & Salovaara, 1978;.…”
Section: Discussionmentioning
confidence: 81%
“…This is mostly within the expected range between 3.7 and 7.1 kg (see review by Reimers, 1997). In Hardangervidda, Skogland (1984) found a mean birth weight of 2.98 kg among 7 dead calves and 3.72 kg among 11 live-captured calves.…”
Section: Discussionmentioning
confidence: 51%
“…They relate both to neonatal mortality and to growth later in life (Lenvik & Aune, 1988;Eloranta & Nieminen, 1986). Among wild reindeer (Rangifer t. tarandus) in southern Norway, mean calving time (the time when 50% of the females have given birth) relates to female body weights in autumn (Reimers, 1997) and possibly to genetic differences (Flydal & Reimers,in press Wildl. Biol.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also likely that summer range is limiting in the NAP because natality in June, and weight and con¬ dition of calves in October has also been low, and these factors are generally considered to be more affected by summer nutrition than by winter nutri¬ tion (cf. Skogland, 1984;Reimers, 1997).…”
Section: Discussionmentioning
confidence: 99%